2015
DOI: 10.4172/2161-1076.1000224
|View full text |Cite
|
Sign up to set email alerts
|

The Prophylaxis and Treatment with Ondansetron for Postoperative Nausea and Vomiting

Abstract: Objective: Postoperative nausea and vomiting (PONV) is the common complication of patients undergoing laparoscopic cholecystectomy (LC). Aim of this study is to determine the efficacy of ondansetron for PONV after LC and exploring the most effective time of using it. Methods: The clinic data of 120 patients with chronic cholecystitis (selected randomly from all the patients undergone LC at the Second Affiliated Hospital of Chongqing Medical University between 2012 and 2014) were analyzed retrospectively. The d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 23 publications
0
6
1
Order By: Relevance
“…Our observation is in line with a similar previous study where Zhang et al 11 (2013) evaluated the role of ondansetron in patients undergoing laparoscopic gynecological surgery and reported that ondansetron considerably reduced the incidence of post-operative nausea (30.0% vs. 55.0%; p-value<0.05) and vomiting (27.5% vs. 55.0%; p-value<0.05) as compared to controls. In another similar trial conducted in patients undergoing general abdominal surgery, Yu et al 14 (2015) also reported similar reduced incidence of vomiting after prophylactic administration of ondansetron (27.5% vs. 50.0%; p-value<0.05) . Similar beneficial effect of preemptive ondansetron has also been reported by Sinha et al 15 in 2004 (20.0% vs. 60.0%; p-value<0.05) and Larijani et al 16 in 1991 (22.0% vs. 72.0%; p-value<0.001) in terms of postoperative vomiting.…”
Section: Discussionmentioning
confidence: 76%
“…Our observation is in line with a similar previous study where Zhang et al 11 (2013) evaluated the role of ondansetron in patients undergoing laparoscopic gynecological surgery and reported that ondansetron considerably reduced the incidence of post-operative nausea (30.0% vs. 55.0%; p-value<0.05) and vomiting (27.5% vs. 55.0%; p-value<0.05) as compared to controls. In another similar trial conducted in patients undergoing general abdominal surgery, Yu et al 14 (2015) also reported similar reduced incidence of vomiting after prophylactic administration of ondansetron (27.5% vs. 50.0%; p-value<0.05) . Similar beneficial effect of preemptive ondansetron has also been reported by Sinha et al 15 in 2004 (20.0% vs. 60.0%; p-value<0.05) and Larijani et al 16 in 1991 (22.0% vs. 72.0%; p-value<0.001) in terms of postoperative vomiting.…”
Section: Discussionmentioning
confidence: 76%
“…The incidence of postoperative nausea or vomiting was higher in patients who received ondansetron just before induction of anaesthesia compared with patients who received the drug shortly before the end of surgery (30 versus 20% and 17 versus 8% for nausea and vomiting, respectively). 18 In a retrospective study of patients undergoing laparoscopic cholecystectomy, 19 8 mg of ondansetron given intravenously during recovery from anaesthesia was associated with a lower incidence of PONV (10%) compared with ondansetron given 30 min before induction of anaesthesia (27%).…”
Section: Discussionmentioning
confidence: 99%
“…These findings are not consistent with those of some other investigations. [17][18][19][20] In a randomised, double-blind, placebo-controlled study, 50 patients undergoing otolaryngological surgery received 4 mg of ondansetron intravenously either before induction of anaesthesia or at the end of surgery a third group of 25 patients served as control. 20 Ondansetron given at the end of surgery significantly reduced the need for rescue antiemetics in the PACU but at 24 h, the incidence of nausea, vomiting and antiemetic requirements did not differ between the three groups.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations